Impact of Patient Counselling Among Type 2 Diabetes Mellitus Patients in a Tertiary Care Hospital - Shailaja K; Asha Anna Thomas; Jerlin R Mathaikutty; Nighil Abraham; Roshni Liza John (International Journal of Pharma and Bio Sciences, 2020)
In India, the number of diabetic patients has increased year by year. One of the reasons was found to be due to poor knowledge regarding the disease and its complications. This can be overcome through patient education. Hence, our study was a Prospective Interventional study carried out in a tertiary care hospital, Chennai for a period of six months to assess the effectiveness of patient counseling in lowering the glycemic levels. A total of 300 patients were screened, of which 262 patients who met the inclusion criteria were equally randomized into Interventional and control group. A well-designed knowledge, attitude and practice questionnaire was administered to both Interventional and control group at baseline (1st month) and at follow up (3rd month). Similarly, blood sugar level and glycated hemoglobin levels were measured at baseline and follow up in both the groups. Patients in the Interventional group received counselling and distribution of pamphlets at the first visit, whereas control group received only at the end of the study. Data were analyzed using the student “t” test. Significant changes (*P valve< 0.0001) in KAP scores, fasting blood sugar, postprandial blood sugar, and glycated hemoglobin were found in the Interventional group whereas no significant changes were observed in the control group. Thus, our study proved that educating the patient would be an added support in lowering glycemic levels in type 2 diabetic patients